The fate and risk of nontuberculous mycobacteria in the water supply system: a review. Issue 2 (7th April 2022) - Gan, Yalan; Rahmatika, Iftita; Kurisu, Futoshi; Furumai, Hiroaki; Simazaki, Dai; Fukano, Hanako; Hoshino, Yoshihiko; Kasuga, Ikuro
Abstract: Nontuberculous mycobacteria (NTM) infection is estimated as the most serious waterborne infectious disease. NTM are ubiquitous in drinking water supply systems, which could be one of the possible exposure pathways for NTM disease, posing a serious concern to human health. Characteristics of NTM, such as exposure via inhalation, disinfectant resistance, survival in oligotrophic conditions, and association with amoebae, are largely different from those of Escherichia coli ( E. coli ) which has been traditionally regarded as a model bacterium causing gastrointestinal diseases in water safety. However, the fate of NTM in water supply systems from source water to the point of use has not been systematically revealed yet. Thus, this review proposes that NTM should be regarded as alternative model bacteria in water use by updating the current knowledge on the occurrence, removal efficiency, and regrowth of NTM in water supply systems. Moreover, we demonstrate the need to establish a comprehensive quantitative microbial risk assessment to identify the critical control point, which is indispensable to mitigate NTM risk in water use. HIGHLIGHTS: Waterborne NTM are posing a significant health threat in many countries. NTM are persistent and can regrow in drinking water, which is so different from traditional model bacterium ( E. coli ). The fate of NTM from source to the point of use remains unclear. Comprehensive risk assessment is lacking for NTM in water supply systems. NTM can be new model bacteria to revisit the management of water supply systems. Graphical Abstract